Implementation of Notary Marking at State-Owned Commercial Banks as High Risk Customers in the Context of Preventing and Eradicating Money Laundering Crimes - Permatarani, Andini Dyahlistia; Sugiharto, R. (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to determine and analyze the mechanisms and legal consequences of the implementation of notary marking at state-owned banks as high-risk customers in the context of preventing and eradicating money laundering crimes. The approach method in this research is sociological juridical. The research specification is analytical descriptive research. The data required includes field study data (field research) taken using the interview method and library research data. The data analysis method uses qualitative data analysis. Based on the research, it was concluded that the mechanism for marking notaries at BUMN Banks as high-risk customers is carried out in 3 (three) stages, namely customer on-boarding, on-going monitoring and post monitoring. Keywords: Bank; Customer; Laundering; Money.